2016
DOI: 10.1016/j.ijheatmasstransfer.2016.02.072
|View full text |Cite
|
Sign up to set email alerts
|

Airside friction and heat transfer characteristics for staggered tube bundle in crossflow configuration with diameters from 0.5 mm to 2.0 mm

Abstract: This article presents new equations for airside friction and heat transfer characteristics for bare tube air-to-refrigerant heat exchangers with tube diameters ranging from 0.5mm to 2mm. There are no airside correlations for such small diameter tubes in the literature. Furthermore, conventional empirical correlation development relies on testing of samples, which is inherently time consuming, expensive and has a limited range of applicability. The correlations presented in this article are developed based on c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…The values of c1–c13 are determined by the number of tubes, using the empirical formula of Daniel Bacellar 10 ; the values are shown in Tables 1 and 2.…”
Section: Methods and Modelsmentioning
confidence: 99%
“…The values of c1–c13 are determined by the number of tubes, using the empirical formula of Daniel Bacellar 10 ; the values are shown in Tables 1 and 2.…”
Section: Methods and Modelsmentioning
confidence: 99%
“…Study the air side friction equation and heat transfer characteristics for bare tube bank air heat exchanger coolers with variations in tube diameter of 0.5-2 mm and pitch ratio of 1.2 -4.0 and air velocity from 0.5 -7.0 m/s in simulation. It turns out that the predictions of the friction equation are more than 80% correlated based on experimental data sources [100]. Based on various studies on staggered bare tube heat exchangers, there is no information regarding the application of staggered bare tube bank heat exchangers as initial air heaters for seaweed convective dryers.…”
Section: Introductionmentioning
confidence: 99%
“…Taler et al 10 combined a nonlinear regression method to determine the correlation coefficient that defines liquid and airside heat transfer. Bacellar et al 11 proposed a framework to study the large design spaces of staggered bundles using automated CFD simulations, and to assess dimensionless thermo‐hydraulic performance on the airside using pipe diameter from 0.5 to 2.0 mm. Bergelin et al 12 reported pressure drop and heat transfer data for vertical tube rows in his study of tubular heat exchangers, providing a preliminary correlation between friction and heat transfer.…”
Section: Introductionmentioning
confidence: 99%